EXECUTIVE-LEVEL DECISION-MAKING IN THE DEVELOPMENT AND OPERATION OF LARGE-SCALE TELECOMMUNICATIONS NETWORKS - Valiienko, Yevhenii Viktorovych (Global Prosperity, 2026)
This study is dedicated to the anatomy of executive-level decision-making under conditions of high uncertainty. The focus lies on the key paradox of modern telecommunications, the so-called "investment scissors" - the necessity of exponentially increasing capital expenditure (CapEx) for the deployment of 5G and fiber optics against a backdrop of stagnating ARPU and the commoditization of traditional services. The paper analyzes how C-level management transitions from deterministic financial models to probabilistic ones (Real Options Analysis) and Smart CapEx strategies. The phenomenon of "organizational ambidexterity" - leadership`s ability to balance the rigorous exploitation of legacy networks with the venture development of innovations - is examined. Particular attention is paid to overcoming the epistemic gap between technical and commercial teams through the implementation of Digital Twins of an Organization (DTO) and Agile transformation. The results show that the long-term viability of an operator depends less on the choice of technologies than on leadership`s ability to build a culture of antifragility, implement a Zero Trust security architecture and accept ethical responsibility for the algorithmic governance of future networks.